Tapping a Hidden Resource : Energy Efficiency in the Middle East and North Africa - World Bank (Washington, DC, 2014)
Energy efficiency can improve fiscal balances, stimulate growth and competitiveness, strengthen energy security, and reduce the energy burden of the poor. It also can enhance the quality of life by improving energy products and services, reducing pollution, and reallocating savings from energy to social services and other welfare enhancements. From a long-term perspective, energy efficiency preserves energy resources for future generations and mitigates climate change. Most governments in the region consider energy efficiency as a priority issue, although for different reasons. The key issue for many is the weight of energy subsidies in fiscal balances; for others, it is the vulnerability of the economy to swings in hydrocarbon prices and the risk of losing competitiveness; and for still others, it is concern about generating enough financing for energy investments and satisfying the energy demand of their fast-growing economies. These factors have prompted governments to renew their efforts to improve energy efficiency. This report explores opportunities to boost energy efficiency in the Middle East and North Africa and secure a sustainable energy future for the region. It explores governments' growing concern about the burden of energy subsidies and identifies opportunities to improve efficiency, drawing on regional and international experience.